Dinamika Komunikasi Kelompok dalam Teori Pertukaran Sosial: Pengaruh Interaksi Interpersonal - M. Diaz Saputra; Wulan Sari Putri; Icha Listya Sitepu (Al-Balagh : Jurnal Komunikasi Islam, 2023)
Social Exchange Theory is based on the principle of economic transactions within social interactions. Its fundamental assumptions involve seeking maximum benefits, human irrationality, limited information, competition, and efforts to achieve both material and immaterial outcomes. In the context of groups, the definition encompasses goals, interdependence, interaction, membership perception, structured relationships, motivation, and beneficial influence. Group communication in the Social Exchange Theory emphasizes the crucial role in exchanging information, resources, and creating balance. Interpersonal interaction, as an effective form of communication between two individuals, forms the foundation for understanding the dynamics of interpersonal communication in this context. Thus, the theory highlights the role of communication in the exchange of information, resources, and the establishment of balance in social interactions.